Graduate Program in Medical Informatics at the University of Utah - Warner, H. R. (Methods of Information in Medicine, 1994)
The graduate student program in medical informatics at the University of Utah described in this paper comprises a Master of Science degree (since 1976) and a Ph.D. degree (since 1962). The average program length is 2 years for M.Sc. and 3-5 years for Ph.D. The aims of the program are to prepare graduates for careers in medical informatics in academic, hospital or industrial settings. There are several different courses of study, or tracks, within the department ranging from Expert Systems, Genetic Epidemiology, Health Care Quality, Hospital Information Systems, Medical Imaging, Medical Physics, to an intensive one-year M.Sc. degree course for physicians. After the first three quarters the students are required to take a qualifying examination in which they qualify for a Masters or Ph.D. degree. The program covers the total spectrum of medical informatics. About 10 students are admitted each year. There are 14 full-time faculty and 9 adjunct faculty. The total number of graduates is 151.
Keywords: Medical Informatics; Graduate Program; Education; Training